Phenotypic characterization of immune cells in fetal tissues of cattle immunized and challenged with Neospora caninum - Rivera Maldonado, Juan E.; Delay, Josepha; Hecker, Yanina; Monterubbianesi, María Gloria; Canton, German Jose; Campero, Carlos Manuel; Odeon, Anselmo Carlos; Moore, Prando Dadin (Elsevier, 2019)
The purpose of this work was to characterize the cellular phenotype in inflammatory infiltrates of fetal tissues from pregnant heifers immunized and experimentally challenged with Neospora caninum. Fetuses from 20 heifers separated into 5 groups were obtained. The experiment was designed as follow: Group A, heifers inoculated intravenously with live tachyzoites of Argentine strain NC-6 (n = 4); Group B heifers inoculated subcutaneously with soluble native antigen from the same strain formulated with immune stimulant complexes (ISCOMs) (n = 4); Group C heifers inoculated with recombinant proteins, rNcSAG1, rNcHSP20, rNcGRA7 formulated with ISCOMs (n = 4), Group D heifers inoculated subcutaneously with sterile phosphate buffered solution (n = 4) and Group E heifers inoculated subcutaneously with antigen-free ISCOMs (n = 4). Experimental challenge was performed at 70 days of gestation and all heifers were euthanized 34 days later. Fetal tissues were taken for histological studies. Inflammatory lesions were observed in brain and lung, and immunhistochemistry was used to identify CD3+, CD20+ and MHC II+ cells. The majority of the cells that infiltrate and circumscribe the lesions in the brain and lung tissue expressed MHC II antigen; varying between 70–90% of the total cellular infiltrate. CD3+ cells were also present within the lesions, contributing to up to 30% of the inflammatory cells. CD20+ cells appeared as a marginal group, in some cases, with a range between 10 and 25%. As expected, the immunolabeling of MHC II + and CD3 + cells in fetal tissues was associated with fetal infection with N. caninum. There were statistically significant differences in the distribution and population of the inflammatory infiltrate in relation to the immunogenic treatment and the type of tissue, with inflammatory cells being markedly less extensive fetuses from group A (dams previously exposed to N. caninum) and in brain tissue. This work showed that Neospora-infection induced MHC II+ and CD3+ cells in bovine fetuses from dams receiving experimental vaccines